Optimalisasi Komunikasi Digital dalam Penerapan Visual Sosial pada Desain atau Layout Website Company Profile - Aisyah Amalia Cahyani; Abdul Kholik; Menati Fajar Rizki (Syntax Corporation Indonesia, 2024)
This research is needed to provide the latest views on the Public Relations and Digital Communication Study Program through online media, namely the website. In addition, in order to increase interaction with the community, especially prospective new students who are looking for information about the Public Relations and Digital Communication study program, as well as to help agencies to continue to adapt to technological developments as an implementation of the implementation of digital communication. This research is a qualitative research with a constructivist approach. The researcher uses constructivists to find out the maximum response of website visitors in disseminating information in the community related to the Study Program through the website. In addition, the constructivist approach was chosen so that researchers have a deeper understanding, not just mere knowledge but are expected to be able to build knowledge and understanding through direct experience and reflection on websites. The implementation of the website development strategy to strengthen the profile of the study program in improving the brand image as one of the applied undergraduate study programs at the State University of Jakarta is a sustainable task and requires continuous efforts to brand this study program to the general public, Personal and Historical Approach to Websites, and Engineering and Aesthetics in the Application of Digital Communication, as well as the Management and Maintenance of Website Development of the Study Program Displaying topics of interest, namely the latest curriculum, topics about curriculum lecturers and topics of graduate job prospects.